The Right to a Clean Tourism Environment: a Perspective on Human Rights and Tourism - Ari Rama, Bagus Gede (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Tourism constitutes a vital economic sector for numerous countries, including Indonesia, with Bali serving as a prominent destination. However, the expansion of this industry has precipitated significant environmental challenges, particularly concerning waste management and environmental sanitation. The right to a clean and healthy environment is recognized as a fundamental human right under various international legal instruments, including the Stockholm Declaration (1972) and the Rio Declaration (1992). In Indonesia, this right is enshrined in Article 28H of the 1945 Constitution and further reinforced by Law No. 32 of 2009 on Environmental Protection and Management. This study employs normative legal research with a comparative approach to assess the consistency of legal frameworks governing the right to a clean tourism environment in Bali and the legal challenges encountered in its implementation compared to other jurisdictions. The findings indicate that despite regulatory measures such as Bali Governor Regulation No. 97 of 2018, which prohibits the use of single-use plastics, enforcement remains hindered by deficiencies in public compliance and waste management infrastructure. A comparative analysis with Japan, Palau, Norway, and Germany underscores that the efficacy of environmental policies is contingent upon a combination of stringent regulations, consistent enforcement mechanisms, and active public participation. Accordingly, an integrative approach—comprising regulatory reinforcement, enhanced public awareness, and innovative environmental management—is imperative to ensure the sustainability of tourism in Bali.